Anti-angiogenic effects of the DPP-4 inhibitor linagliptin via inhibition of VEGFR signalling in the mouse model of oxygen-induced retinopathy - Kolibabka, Matthias; Dietrich, Nadine; Hammes, Hans-Peter (Diabetologia, 2018)
Linagliptin has protective effects on the retinal neurovascular unit but, in proliferative retinopathy, dipeptidyl peptidase 4 (DPP-4) inhibition could be detrimental. The aim of this study was to assess the effect of linagliptin on ischaemiainduced neovascularisation of the retina.
Gesehen am 13.12.2019